Perbandingan Akhlak Siswa Berasrama dengan Non Asrama SMA Boarding School - Suntiah, Ratu; Fikri, Miftahul; Assidiqi, Muhammad Hasby (Atthulab: Islamic Religion Teaching and Learning Journal, 2020)
The study aims to find out the moral difference between boarding students and non-dorm students. This research is a quantitative study with a comparative design of two free variables with survey research design. Poll instruments are disseminated with the provisions of accidental sampling techniques. The results showed that the quality of the boarding school students received a total score of 95.14 with an average of 3.8 and a percentage worth 76%. Meanwhile, the quality of non-dorm students get a total score of 91 with an average of 3.64, a percentage worth 73%. Comparative quality of dormitory students with non-dormitories only 3%. Then the hypotheses submitted correspond to the results of the study, although not reaching a significant level. This shows the role that dormitories have very few positive impacts and increasing student morality is no easy thing. Because of moral enhancement even in the slightest level it is invaluable to be safeguarded and to add hope to improve the student's moral potential better and still many aspects that can be improved through the boarding system.Â Penelitian ini bertujuan untuk mengetahui perbedaan akhlak antara siswa berasrama dengan siswa non asrama. Penelitian ini merupakan peneltian kuantitatif dengan jenis rancangan komparatif dua variabel bebas dengan desain penelitian survei. Instrumen angket yang disebarkan dengan ketentuan teknik sampling aksidental. Hasil penelitian menunjukan bahwa kualitas akhlak siswa berasrama mendapatkan skor total 95,14 dengan rata-rata 3,8 dan persentase senilai 76%. Sementara itu, kualitas akhlak siswa non-asrama mendapatkan skor totalÂ 91 denganÂ rata-rata 3,64, persentase senilai 73%. Kualitas perbandingan akhlak siswa asrama dengan non-asrama hanya 3%. Maka hipotesis yang diajukan sesuai dengan hasil penelitian, walaupun tidak mencapai taraf yang signifikan. Hal ini menunjukan peran asrama memiliki dampak positif yang sangat sedikit dan meningkatkan akhlak siswa bukanlah perkara mudah. Sebab peningkatan akhlak walaupun dalam taraf yang sedikit itu sangat berharga untuk dijaga serta menambah harapan untuk meningkatkan potensi akhlak siswa lebih baik lagi, serta masih banyak aspek yang bisa ditingkatkan melalui sistem asrama.